Perceptions of Customers Toward Business Capital Financing Provided by Bank Syariah Indonesia (BSI) in West Aceh Regency - Salma, Salma; Hendrawan, Yoni; Rinaldi, Mikhral (Jurnal Ilmiah Global Education, 2025)
This study seeks to examine customer opinions of Bank Syariah Indonesia (BSI) business capital finance in West Aceh Regency. This study employs a qualitative methodology utilising in-depth interviews with seven informants purposefully recruited from diverse business sectors. The results indicate that most customers have a positive perception of BSI’s financing, particularly regarding procedural ease, contract transparency, flexible installment tenors, and positive impacts on business growth. However, varied experiences were found concerning post-disbursement services. The discussion connects these findings with the Theory of Planned Behavior and prior studies, emphasizing that positive perceptions are shaped through the integration of functional, procedural, and relational dimensions. This study concludes that BSI’s financing model represents a participatory and contextual application of Islamic finance and offers strategic implications for strengthening service models based on local values.